First Day Cover commemorating the 75th anniversary of the American Chemical Society - Fleetwood (1951)
Cachet created by Fleetwood depicts "The Chemist" along with ACS logo and the tagline, "Maker of a Better Tomorrow." Stamp issued to commemorate the diamond jubilee of the American Chemical Society. Addressed to and signed by Roger Adams.
Keywords: Postage stamps; Chemistry; Chemists; Postmarks; Adams, Roger, 1889-1971; American Chemical Society; Science on postage stamps; Cachets (Philately); First day covers (Philately)